A new snow removal device and determination of for membrane structures. Issue 1 (June 2021) - Wang, B S; Zhang, Y K; Meng, L; Li, S; Zhang, H; Song, Q H
Abstract: In order to avoid the damage of membrane structure caused by snow load, a new type of intelligent snow removal device is proposed based on the principle of micro-spray irrigation and the dual control of pressure and temperature. The determination method of construction parameters such as pressure critical value, snow area, sprinkler size and number of the device is expounded. Finally, taking a Shanghai membrane structure project as an example, the snow area of the project was determined. Considering the size of snow area and the sprinkler spraying area, the number and construction location of the sprinklers on the membrane surface were finally determined.